Structure, function, and regulation of Escherichia coli rRNA in Proteus mirabilis. - Morgan, E A (1978)
Escherichia coli rRNA genes have been introduced into Proteus mirabilis on an F-prime factor (F'14). A portion of the ribosomes in the resulting merodiploid consist of E. coli rRNA and P. mirabilis ribosomal proteins. These ribosomes are structurally similar to normal P. mirabilis or E. coli ribosomes and exhibit many or all of the functional properties of normal ribosomes. The accumulation of E. coli rRNA in the merodiploid is regulated in a way similar to the the regulation of P. mirabilis rRNA.